1984
DOI: 10.1002/ijc.2910340219
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of murine tumor necrosis factor (TNF) against transplanted murine tumors and heterotransplanted human tumors in nude mice

Abstract: The antitumor activity of highly purified tumor necrosis factor (TNF) was tested against eight kinds of murine tumor and five kinds of human tumor heterotransplanted into nude mice. Mice were treated by intravenous or intratumoral injection of TNF, commencing when the tumors were well established. TNF showed an excellent curative effect against all kinds of murine and human tumors tested. Meth A sarcoma, Colon 26, Ehrlich, sarcoma 180, MM 46, MH 134, B16 melanoma, and Lewis lung tumors transplanted into mice u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
98
0
2

Year Published

1989
1989
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(102 citation statements)
references
References 9 publications
2
98
0
2
Order By: Relevance
“…Activated monocytes are known to secrete cytokines such as tumour necrosis factor alpha (TNF-a) (Carswell et al. 1975: Haranaka et al. 1984: Feinman et al.…”
mentioning
confidence: 99%
“…Activated monocytes are known to secrete cytokines such as tumour necrosis factor alpha (TNF-a) (Carswell et al. 1975: Haranaka et al. 1984: Feinman et al.…”
mentioning
confidence: 99%
“…This observation supports previous findings that both gene-cloned and natural TNF elicits significant necrotic responses of Meth A-bearing BALB/c mice with single administration intralesionally or i.v. (Carswell et al 1975;Haranaka et al 1984;Pennica et al 1984). Hayashi et al (1986) reported that when rTNF was administrated i.v., rTNF markedly accumulates the tumor tissue and the half life Carswell et al (1975) reported that the maximal necrotic response induced by serum containing TNF was observed on day 7 at which the transplants were established well, and less effective on day 5 or 6.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-tumor activity against solid tumors was expressed as mean tumor weights. Tumor weight, as derived from caliper measurements of the length (L) and width (W) of the tumors, and the length (l) and width (w) of tumor necrosis in mm, was calculated as follows 26 :…”
Section: Methodsmentioning
confidence: 99%